Presupuesto del gobierno autónomo descentralizado parroquial rural de la unión durante el periodo 2019 – 2020 - Quijano Lamilla, Evelyn Jamileth (2022)
The budget is one of the most used tools to foresee the future of an entity, helps to set short and long-term goals, and above all is influential in decision making. If a company does not have a budget, it will not be able to execute its action plans nor will it be able to make a profit. The budget within the Decentralized Autonomous Governments helps to ensure that the works are executed for the benefit of citizens and to control public expenditures. The public budget is made up of three important items: Revenue, Expenses and General Provisions. Each of these items provide an important value within the budget, allow the budget execution to be equitable and that the resources are allocated to the works that help citizens. In the same way, citizens deserve to know what is the budget that each GAD has, its percentages of execution and the value of each item. That is why the purpose of this case study is to publicize the Budget of the Decentralized Autonomous Rural Parish Government of La Union, to know more about the items that make it up, their respective values, their use, their percentage of execution and to know what their distribution was during the period 2019 – 2020.